Applications of Edible Coatings Formulated with Antimicrobials Inhibit Listeria monocytogenes Growth on Queso Fresco - Brown, Stephanie R. B.; Kozak, Sarah M.; D’Amico, Dennis J. (Frontiers in Sustainable Food Systems, 2018)
Despite efforts to control Listeria monocytogenes in dairy processing environments, contamination and subsequent outbreaks of listeriosis continue to occur. The ability of L. monocytogenes to grow during refrigerated storage necessitates strategies to prevent contamination, reduce pathogen numbers, and limit growth during storage. The objective of this study was to determine the efficacy of edible antimicrobial coatings to control L. monocytogenes on Queso Fresco (QF) when applied before [precoated (PC)] or after [preinoculated (PI)] surface contamination. Coating solutions were formulated to contain 2% chitosan and either 5% hydrogen peroxide (HP), 5% lauric arginate (LAE), 25% acidified calcium sulfate with lactic acid (ACSL), or combinations of 10% sodium caprylate (SC) with either LAE or ACSL. Fresh QF samples (25 g) were inoculated with L. monocytogenes at 4 log CFU/g prior to, or following, antimicrobial coating application. Cheeses were then vacuum packaged and stored at 7°C for 35 days with weekly enumeration of L. monocytogenes. Aside from ACSL and LAE + SC, there was no effect of coating application timing (PC vs. PI) on the change in L. monocytogenes counts over time. Chitosan coatings without additional antimicrobials were more effective than controls but did not inhibit L. monocytogenes growth beyond 7 days. Coatings containing HP at 5% were equally effective when applied before or after L. monocytogenes inoculation, significantly reducing L. monocytogenes counts by more than 3 log CFU/g and inhibiting growth through 35 days of storage. Coatings formulated with ACSL at 25% were more effective when applied to PI cheeses but neither application produced significant reductions in L. monocytogenes counts or inhibited growth. Although LAE coatings were more effective than ACSL, neither were more effective than chitosan coatings alone. The addition of SC to ACSL and LAE coatings enhanced their antimicrobial activity as ACSL + SC and LAE + SC coatings reduced L. monocytogenes counts by >1 log CFU/g after 24 h and were listeristatic through 28 and 35 days, respectively. The identification of listericidal and listeristatic edible antimicrobial coating applications that are effective when applied before or after contamination events identifies a new approach for the control of L. monocytogenes on fresh cheese.